El ingreso proveniente del trabajo y el número de trabajadores del sector privado en Loreto periodo 2017 – 2021 - Arévalo Vargas, Elmer Roldán (2024)
In general, the private sector is the main generator of employment in the labor market and the one that provides higher salaries than those offered by the public sector; Furthermore, the State has to be small but agile and modern. This doctoral thesis aims to determine the relationship between the level of income from work and the number of workers in the private sector in Loreto, in the period 2017 - 2021. The methodology used indicates that it is a Correlational type of research, supported by a Non-Experimental design. The conclusions of the study are that there is no relationship between the average income that comes from work and the number of workers in the private sector of Loreto, because the Correlation Coefficient was r = 0.616767192; and the Coefficient of Determination was R2 = 0.390401770. The majority of the employed population has been working in the Public Sector (93.42%), so the State is the main employer, while the Private Sector only employed 6.58% of the workforce. On the other hand, the evolution of employment in the private sector was marked by ups and downs from one year to the next, with the largest number of workers having been employed in 2019, reaching 35,859 people, and then dropping abruptly in 2020 to 32,224.00 products. of the crisis caused by the COVID 19 pandemic. Likewise, Male workers (S/. 1,235.30) earn more than Female workers (S/. 1,091.56).